PENGARUH PENGETAHUAN TENTANG HUKUM LINGKUNGAN DAN PENILAIAN ATAS REGULASI PEMERINTAH TERHADAP PARTISIPASI PELAKU INDUSTRI DALAM MENGELOLA KAWASAN INDUSTRI DI KOTA SINGKAWANG - Rudi Agustian Hassim (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2010)
The objective of this research is to analyze the effects of knowledge about environmental law andassessment of government regulations on industrial doers’ participation in managing the industrial area inSingkawang city. The sample of this research were 48 persons which randomly taken. The data were analyzed byusing ANAVA 2 X 2. Findings of the research indicated that the industrial doers who were knowledgeable aboutenvironmental law and had positive assessment of government regulations participated better in industrialmanagement than those who had negative assessment. Therefore, the two variables should be taken intoconsideration to increase the doers’ participation in managing industrial area.